Thaipusam in Malaysia: a Hindu festival in the Tamil diaspora - Belle, Carl Vadivella (ISEAS, Yusof Ishak Institute, 2017)
Indians in Malaysia, the social and ethnic context -- Tamil traditions and South Indian Hinduism -- Colonialism, colonial knowledge and Hindu reform movements -- 4. Hinduism in Malaysia, an overview -- Murugan, a Tamil deity -- Phenomenology of Thaipusam at Batu Caves -- Other Thaipusams -- Thaipusam considered, the divine crossing